Analysis of Maternal Factors Affecting The Incidence of Low Birth Weight (LBW) at Kanor Health Center, Bojonegoro, Regency, East Java. - Zulfa Nurusyafa Arofatulloh, - (International Journal of Research Publications, 2021)
Abstract Background: Low birth weight (LBW) babies are one of the health problems that are a serious concern in several developing countries. Low birth weight (LBW) is a condition when a baby is born weighing < 2500 grams. LBW contributes 60%-80% of all neonatal deaths in the world. LBW can be caused by factors originating from the mother, fetus or from the surrounding environment. This study aims to analyze maternal factors that influence the incidence of low birth weight (LBW) babies at Kanor Health Center, Bojonegoro, East Java. Methods: This research method is observational analytic with a case control research approach. The number of samples was 52 (26 groups of cases and 26 control groups), the sampling technique of the case group used total sampling and the control group used simple random sampling with the determination of inclusion criteria and exclusion criteria. The independent variables were Chronic Energy Deficiency (CED), maternal weight gain during pregnancy, gestational age at birth, comorbidities (anemia and pre-eclampsia), parity, pregnancy interval, and frequency of Antenatal Care (ANC). The dependent variable consisted of the case group (LBW) and the control group (Not LBW). The research data is secondary data in the from of a cohort of mothers and toddlers in January-December 2020. Data analysis is in the form of univariate and bivariate analysis. Statistical tests in the form of Chi-Square test and Fisher's Exact Test. Results: statistical test results obtained Chronic Energy Deficiency (CED) status p(sig)=0,100, maternal weight gain during pregnancy p(sig)=0,006, gestational age at birth p(sig)=0.014, comorbidities (anemia and preeclampsia) anemia p(sig)=1.247 and preeclampsia p(sig)=0.490, parity p(sig) = 0.554, gestational interval p(sig)=0.056, frequency of Antenatal Care (ANC) p(sig)=0.026. Conclusion: there is a correlation between maternal weight gain during pregnancy, gestational age at birth and frequency of Antenatal Care (ANC) and there is no significant correlation between Chronic Energy Deficiency (CED), comorbidities (anemia and preeclampsia), parity and distance pregnancy on the incidence of LBW at Kanor Health Center, Bojonegoro , East Java.